The NBC Advisory Council and Radio Programming, 1926-1945. (Southern Illinois University Press, 2009)
In 1926, the new NBC networks established an advisory board of prominent citizens to help it make program decisions as well as to deflect concerns over NBC's dominance over radio. The council, which advised NBC on program development-especially cultural broadcasts and those aimed at rural audiences-influenced not only NBC's policies but also decisions other radio organizations made, decisions that resonate in today's electronic mediaThe council's rulings had wide-ranging impact on society and the radio industry, addressing such issues as radio's operation in the public int.